New pesticides and agro-chemicals in technology of cultivation of naked oat Vyatsky - T. K. Sheshegova; G. A. Batalova; L. M. Shchekleina; I. I. Rusakova (Аграрная наука Евро-Северо-Востока, 2016)
The influence of biological preparations Emistim, Zirkon, Siliplant and Streptomyces hygroscopicus strain A-4 on phytosanitary status of plants and grains, grain yield, fresh and dry matter yield of naked oat Vyatsky was studied in the field and laboratory (in vitro) experiments. Biological preparations were used separately for treatment of seeds and plants at tillering phase and in mixture with chemical fungicide Dividend star for seed treatment. Plot area was 5 m2, 3 replications, in microbiological research - 5 replications. It was shown that growth regulator Emistim and St. hygroscopicus strain A-4 are most effective in cultivation technology of naked oat Vyatsky. Preparation Emistim per se and in mixture with fungicide Dividend star significantly reduced development of fusariosis (root rot, fusariosis of panicle) and helminthosporiosis (red-brown spot) diseases. Using of spore suspension of St. hygroscopicus strain A-4 is effective for phytosanitary purposes at plant treatment at tillering phase. Potentially pathogenic fungi Alternaria spp . (34.1%), Cladosporium spp . (11.8%), Penicillium spp . (22.4%) etc. prevailed (88.5%) in contaminant of newly grains, part of Fusarium spp . species was less than 10%. Studied preparations positively influenced on production processes in naked oat. Addition grain, fresh and matter yield was from 4 up to 106% relative to control on average for two years. This property of active substances of preparations is most evident in unfavorable growth conditions. For example, in dry 2013 significant addition grain yield was obtained in 14 variants of experiment from 15; fresh yield - in 6; dry matter - in 10; in 2014 with sufficient moistening they was not significant despite higher yield. It was established that significant influence on grain yield was provided not only by using preparations but also by diseases: root rot (r = -0.49) and stem rust (r = -0.42).